Core musculature co-contraction during suspension training exercises. (April 2022) - Jordan, Shannon L.; Brinkman, Brandi; Harris, Sean; Cole, Taylor; Ortiz, Alexis
Abstract: Suspension training reportedly enhances core musculature co-contraction. This study investigated whether the use of a suspension trainer increases core musculature co-activation during exercises vs. its floor counterpart. Participants were 25 healthy volunteers (16 men, 9 women; age: 27.24 ± 4.02 years). Wireless electromyography electrodes were placed bilaterally at the rectus abdominis (RA), erector spinae (ES), and abdominal obliques (OB). Test order (push-up, bridge, and prone plank) was randomized (exercise and condition) with a 3-min rest period between tests. Co-contraction ratios between muscle groups were estimated by root mean square. Ratios (RA/ES, RA/OB, ES/OB) were analyzed using paired t-tests (P ≤ .05). For all floor exercises, co-contraction of core musculature was significantly higher than suspension trainer. During suspension training, perturbations due to increased agonist activation without similar increases in antagonists may be too intense for untrained or injured individuals. Individuals lacking muscle control to recruit muscles concurrently may benefit from mastering traditional floor exercises to promote joint stiffness and stability before suspension trainer exercises. Highlights: Suspension training (ST) reportedly enhances core musculature co-contraction. Co-contraction of core musculature was higher in floor exercises vs. suspension trainer. ST Perturbations may be too intense for untrained or injured persons. Individuals lacking muscle control should master floor exercises prior to ST exercises.